Quality of the working environment : an overview of the current situation in the Slovak Republic - Piňosová, Miriama (Array, 2021)
For the individual and for society, human life and health are great values, which are often particularly difficult or impossible to measure, though they are irreplaceable values. Even in the oldest historical stages of the development and life of society, many important doctors and scientists were interested in the social aspects of health care, e.g. Hippocrates, Aristotle, Avicenna. Paracelsus († 1541, Swiss philosopher and physician) and Georgius Agricola († 1555, German chemist and mineralogist). Based on their own experience gained from daily contact with workers and their working environment, they examined disorders caused by the harmful factors of the working environment and working processes. The ever-changing world of work increasingly brings new risks into working processes, which are directly related to the work performed by employees. As part of the EU-OSHA (European Agency for Safety and Health at Work) strategy to increase health and safety at work, the European Risk Observatory called on EU Member States to improve the detection of these risks in the working environment. Considering the above, the authors of this article have set themselves the goal of mapping the current situation in the area of the creation, protection and quality management of the working environment. They describe general requirements for protecting occupational health and safety, mainly in Slovakia. They are convinced that current developments present the need to know as much as possible about the living and working environments, to have a thorough knowledge of working conditions and all the factors that affect the health of employees, to know and choose assessment procedures to reduce the negative effects of these factors to a minimum. It is important that we keep in mind that healthy working conditions are among the most valuable assets of individuals, communities and nations.